THE BACTERICIDAL ACTION OF PROPYLENE GLYCOL VAPOR ON MICROORGANISMS SUSPENDED IN AIR. I - Robertson, O. H. (The Rockefeller University Press, 1942)
It has been found that propylene glycol vapor dispersed into the air of an enclosed space produces a marked and rapid bactericidal effect on microorganisms introduced into such an atmosphere in droplet form. Concentrations of 1 gm. of propylene glycol vapor in two to four million cc. of air produced immediate and complete sterilization of air into which pneumococci, streptococci, staphylococci, H. influenzae, and other microorganisms as well as influenza virus had been sprayed. With lesser concentrations of propylene glycol, rapid and marked reduction in the number of air-borne bacteria occurred, but complete sterilization of the air required a certain interval of time. Pronounced effects on both pneumococci and hemolytic streptococci were observed when concentrations as low as 1 gm. of glycol to fifty million cc. of air were employed. Numerous control tests showed that failure of the glycol-treated microorganisms to grow on the agar plates was due to actual death of the bacteria. The means by which propylene glycol vapor produces its effect on droplet-borne bacteria is discussed and data relating the bactericidal properties of propylene glycol in vitro to the lethal action of its vapor is presented. Atmospheres containing propylene glycol vapor are invisible, odorless, and non-irritating. This glycol is essentially non-toxic when given orally and intravenously. Tests on possible deleterious effects of breathing propylene glycol containing atmospheres over long periods of time are being carried out.